TRENDS OF COSMETICS AND KOREAN FOOD AND ITS HALAL STATUS IN INDONESIAN TEENAGER PERSPECTIVE: A LITERATURE REVIEW - Ramadhani, Khairunisa; Widyaningrum, Rachmawati; Khofifa, Hesti; Rahma, Sita Fauzia; Setiawan, Yuni Wahyuningsih (Jurnal Ilmu Kesehatan Masyarakat, 2023)
Indonesia is a country in Southeast Asia which dominated by Muslim population. This condition brings halal products to have a very large market share potential, especially food and cosmetic products. A large number of Muslim consumers in Indonesia raises new challenges with the high public interest in Korean food and cosmetics products, which some types of products do not have a halal label. Because Korea is not a Muslim country, most of the imported products are not halal. That condition could be marked as the importance of awareness towards imported products that have non-halal status risk. Furthermore, due to the research limitation of Indonesian teenagers’ perspective about halal status, we need to provide more certain information about halal status. The method for this study uses a literature review by searching for a literature database obtained from the Google Scholar search engine with inclusion criteria such as articles in English or Indonesian, published between 2011-2021, accessible in full text, and articles discussing the halal status of Korean products and adolescent perspective. Indonesia, especially Muslim teenagers towards Korean cosmetic and food products. The results show that Indonesian teenagers’ huge interest in Korean products, the product’s halal status is one of the factors that affect teenagers' intention to buy Korean food and cosmetics and it works as a key factor/their priority in purchasing products. Teenagers are concerned about the halal status of Korean food and this aspect becomes a priority when buying Korean food. The conclusion of this study is that the halal status of Korean food and cosmetic products has an effect on consumer buying interest.